DETERMINATION OF THE ACTIVE COMPOUNDS IN THE EXTRACT OF THE BERBERIS VULGARIS LEAVES PREPARATION FOR ITS APPLICATION TO PREVENT A PEPTIC GASTRIC ULCER - Marina, Kapitonova; Renad Nikolaevich, Alyautdin; Svetlana Lvovna, Morokhina; Ekaterina Vyacheslavovna, Sergunova; Imam Bux, Brohi; Saiful Bahri, Talip; Norhida, Ramli; Abdel Aziz Ibrahim, Ibrahim (Avicenna Tajik State Medical University, National Academy of Sciences of Tajikistan, 2025)
Peptic ulcer disease is a chronic condition with high prevalence, which is being treated by numerous gastroprotective drugs with a few side effects and adverse influences on the pharmacokinetics of comedications. Therefore, traditional medicine becomes a high demand in treating this disorder. Numerous herbal medications are used to treat diseases of the gastrointestinal tract (GIT). Among them, Berberis vulgaris plays an important role, as its fruit extract was shown to have antioxidant properties and antimicrobial activity against the causative agent H. pylori. Objective: To establish a reliable method of preparing Berberis vulgaris leaves extract and determining its active components. Material and methods: The spectrophotometric method was used to determine the active components in the alcohol extract of Berberis vulgaris leaves extract. Results: Chemical analysis showed that the Berberis vulgaris leaf extract contains 0.48±0.09% of flavonoids, 0.07±0,02% of alkaloids, and 8.05±0.17% of tanning substances, which make it suitable for application as prevention of gastric ulcer development. Conclusion: This study established an efficient, sensitive, and selective method for simultaneous determination of the flavonoids, alkaloids, and tanning substances in the Berberis vulgaris leaves extract, which could be successfully applied to prevent gastric ulcer development in preclinical trials.